The Grammar of Honour and Revenge - Aase, Tor H. (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
There is a rich anthropological literature on honour and revenge, but more often than not, analyses are limited to cultural or historical expressions of the phenomena. As a corollary, the recent re-emergence of honour in Europe is usually explained in terms of non-western immigrants who bring notions of honour as part of their cultural luggage. However, the practice of honour and revenge by Danish Motorcycle Clubs suggests that such an approach is insufficient. The ambition in the article is to go beyond the various cultural expressions and search for a basic ‘grammar’ that can explain why honour becomes a valid theme in some societies and in certain situations. In that endeavour, two questions are vital: What is honour all about? And what is the logic in the perception that lost honour can be restored through revenge? Analysis of a prototypical feuding community in Northern Pakistan concludes that honour is best understood as a family’s publicly recognized capability for self-defence, and that revenge is a means to restore that image if it has been shattered. I contend that honour – in the sense of self-defence – is vital in societies where there is no accessible level of appeal in cases of conflict. Furthermore, the logic of honour that prevails among competing families in Northern Pakistan can also occasionally be recognized at the state level in international politics since there is no reliable supranational level of appeal in cases of perceived injustice.